Mary's bodily Assumption - Levering, Matthew, 1971- (Notre Dame, Indiana : University of Notre Dame Press, 2015)
In Mary's Bodily Assumption, Matthew Levering presents a contemporary explanation and defense of the Catholic doctrine of Mary's bodily Assumption.
Introduction -- Twentieth-century magisterial teaching on Mary and her Assumption -- Early to mid-twentieth-century theologies of Mary's Assumption -- The Nouvelle théologie and Mary's Assumption -- The validity and scope of typological exegesis -- The authority of the Church as interpreter of revelation -- The fittingness of Mary's Assumption in God's economy of salvation -- Conclusion.
Includes bibliographical references and index.
English.
Print version record.
JSTOR
Keywords: Mary, -- Blessed Virgin, Saint -- Assumption; Catholic Church -- Doctrines; Marie, -- Sainte Vierge -- Assomption; Église catholique -- Doctrines; Mary, -- Blessed Virgin, Saint; Catholic Church; RELIGION -- Christian Theology -- Mariology; Assumption of the Blessed Virgin Mary; Theology, Doctrinal